Corporate Law Firms and the Perversion of Justice: What Public Interest Lawyers Can Do About It - Ralph Nader (Washington University Journal of Law & Policy, 1999)
Law schools today have greatly improved over the past forty years. The question is if they have improved enough.
Keywords: Corporate counsel; Public interest law